Ceruloplasmin Plays a Neuroprotective Role in Cerebral Ischemia - Ryan, Fari; Zarruk, Juan G.; Lößlein, Lena; David, Samuel (Frontiers in Neuroscience, 2019)
Ceruloplasmin (Cp) is a ferroxidase that also plays a role in iron efflux from cells. It can thus help to regulate cellular iron homeostasis. In the CNS, Cp is expressed as a membrane-anchored form by astrocytes. Here we assessed the role of Cp in permanent middle cerebral artery occlusion (pMCAO) comparing wildtype and Cp null mice. Our studies show that the lesion size is larger and functional recovery impaired in Cp null mice compared to wildtype mice. Expression of Cp increased 9-fold at 72h after pMCAO and remained elevated about 2-fold at day 14. We also assessed changes in mRNA and protein expression of molecules involved in iron homeostasis. As expected there was a reduction in ferroportin in Cp null mice at 72h. There was also a remarkable increase in DMT1 protein in both genotypes at 72h, being much higher in wildtype mice (19.5-fold), that then remained elevated about 2-fold at 14d. No difference was seen in transferrin receptor 1 (TfR1) expression, except a small reduction in wildtype mice at 72h, suggesting that the increase in DMT1 may underlie iron uptake independent of TfR1-endosomal uptake. There was also an increase of ferritin light chain in both genotypes. Iron histochemistry showed increased iron accumulation after pMCAO, initially along the lesion border and later throughout the lesion. Immunofluorescence labeling for ferritin (a surrogate marker for iron) and GFAP or CD11b showed increased ferritin in GFAP+ astrocytes along the lesion border in Cp null mice, while CD11b+ macrophages expressed ferritin equally in both genotypes. Increased lipid peroxidation assessed by 4HNE staining was increased 3-fold in Cp null mice at 72h after pMCAO; and 3-nitrotyrosine labeling showed a similar trend. Three key pro-inflammatory cytokines (IL-1β, TNFα, and IL-6) were markedly increased at 24h after pMCAO equally in both genotypes, and remained elevated at lower levels later, indicating that the lack of Cp does not alter key inflammatory cytokine expression after pMCAO. These data indicate that Cp expression is rapidly upregulated after pMCAO, and loss of Cp results in dysregulation of iron homeostasis, increased oxidative damage, greater lesion size and impaired recovery of function.